Performance evaluation of a direct-conversion flat-panel detector system in imaging and quality assurance for a high-dose-rate 192Ir source. (7th March 2018) - Miyahara, Yoshinori; Hara, Yuki; Nakashima, Hiroto; Nishimura, Tomonori; Itakura, Kanae; Inomata, Taisuke; Kitagaki, Hajime
Abstract: In high-dose-rate (HDR) brachytherapy, a direct-conversion flat-panel detector (d-FPD) clearly depicts a 192 Ir source without image halation, even under the emission of high-energy gamma rays. However, it was unknown why iridium is visible when using a d-FPD. The purpose of this study was to clarify the reasons for visibility of the source core based on physical imaging characteristics, including the modulation transfer functions (MTF), noise power spectral (NPS), contrast transfer functions, and linearity of d-FPD to high-energy gamma rays. The acquired data included: x-rays, [ X ]; gamma rays, [ γ ]; dual rays ( X   +   γ ), [ D ], and subtracted data for depicting the source ([ D ]  −  [ γ ]). In the quality assurance (QA) test for the positional accuracy of a source core, the coordinates of each dwelling point were compared between the planned and actual source core positions using a CT/MR-compatible ovoid applicator and a Fletcher–Williamson applicator. The profile curves of [ X ] and ([ D ]  −  [ γ ]) matched well on MTF and NPS. The contrast resolutions of [ D ] and [ X ] were equivalent. A strongly positive linear correlation was found between the output data of [ γ ] and source strength ( r 2   >  0.99). With regard to the accuracy of the source core position, the largest coordinate difference (3D distance) was noted at the maximum curvature of the CT/MR-compatible ovoid and Fletcher–Williamson applicators, showing 1.74  ±  0.02 mm and 1.01  ±  0.01 mm, respectively. A d-FPD system provides high-quality images of a source, even when high-energy gamma rays are emitted to the detector, and positional accuracy tests with clinical applicators are useful in identifying source positions (source movements) within the applicator for QA.